2015
DOI: 10.4238/2015.april.17.9
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Diversity of TNF-α region in Chinese domestic goats

Abstract: ABSTRACT. Tumor necrosis factor-a is a cytokine with a wide range of effects on both lymphoid and non-lymphoid cells. In this study, we identified polymorphisms in major histocompatibility complex class III gene in the 4th exon and the 3' untranslated region of tumor necrosis factor-a to evaluate the immunogenetic diversity of Chinese south indigenous goat. Three single-nucleotide polymorphisms were identified and showed similar frequencies in different except MI loci. These data suggest that the high immunodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The primary role of TNF is in the regulation of immune cells. A recent study examined the diversity in the TNF- α exon 4 and 3'UTR in native Chinese domestic goats and three SNPs in the 3'UTR region [ 44 ] were identified. However, an investigation on North American goat breeds revealed that the same analyzed SNPs of TNF- α were monomorphic [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of TNF is in the regulation of immune cells. A recent study examined the diversity in the TNF- α exon 4 and 3'UTR in native Chinese domestic goats and three SNPs in the 3'UTR region [ 44 ] were identified. However, an investigation on North American goat breeds revealed that the same analyzed SNPs of TNF- α were monomorphic [ 45 ].…”
Section: Discussionmentioning
confidence: 99%